2D Structures Exhibiting Negative Area Compressibility. Issue 12 (9th October 2017) - Lim, Teik‐Cheng
Abstract : This paper proposes an in‐plane negative area compressibility (NAC) material not due to Lifshitz mode, but due to all around in‐plane pressure. The NAC system consists of an array of two‐dimensional material in the form of n ‐sided polygon with n /2 number of connecting rods, where n is an even number. Two types of NAC microstructural geometries are introduced herein: 8‐sided polygon in square array and 6‐sided polygon in hexagonal array. The polygons are permitted to change in shape – and hence change in area – at constant side lengths with accompanying translational motion of the connecting rods, thereby changing the overall area of the cell. Results reveal that negative compressibility is observed in the square array NAC when the material shape is in between a regular octagon and a square, and in the hexagonal array NAC when the material shape is in between a regular hexagon and an equilateral triangle. Abstract : This work reports a concept of negative area compressibility based on 2D lattices of octagonal conventional material linked with four neighbors and hexagonal conventional material linked with three neighbors. Application of in‐plane pressure reduces the polygonal material area through bending of the hinges. Simultaneously, the hinges are being pushed out such that the distance between neighboring polygonal materials increases.